Does CEO education influence the target leverage and speed of adjustment? - Chua, Mei Shan; Ab Razak, Nazrul Hisyam; Md Nassir, Annuar; Yahya, Mohamed Hisham (Innovare Academics Sciences, 2020)
This study addresses the importance of unobservable factor (CEO education) as the determinant of firm leverage along two stages: target leverage and speed of adjustment towards target leverage. Based on two-step GMM system, this study sheds light on the role of CEO education in these two stages and reveals how it influences the firms’ total leverage, long-term leverage and short-term leverage. In the first stage, the results indicate that CEOs education is negatively associated with firms’ leverage that measures by total leverage and long-term leverage; meanwhile, it has a positive impact on short-term leverage. In the second stage, CEOs’ education is only positively related to the speed of adjustment towards short-term leverage. The reason for this is that when the cost of financial capital is high, highly educated CEOs are more entrenched to use more leverage. Furthermore, when the cost of adjustment is low, highly educated CEOs perceive that the benefits of adjusting towards target leverage exceed the costs of adjusting towards target leverage. The results are consistent with the Upper Echelons Theory regarding the reflection of the CEOs on the firms' strategic decisions. Taken together, this paper findings highlight the importance of considering unobservable factors into account when examining the firm leverage, which has received relatively little attention to date.